FACTORS INFLUENCING UTILISATION OF FAMILY PLANNING SERVICES AMONG WOMEN OF REPRODUCTIVE AGE AT FORT PORTAL REGIONAL REFERRAL HOSPITAL KABAROLE DISTRICT. A DESCRIPTIVE CROSS-SECTIONAL STUDY. - IVAN MUHIMBO (Student's Journal of Health Research, 2023)
Introduction Family planning has been implemented in Uganda though its utilization has reduced, this study was meant to determine factors influencing the utilization of FP among women of reproductive age. Objectives This study was aimed at determining the knowledge, health-related factors, and socio-economic factors influencing the utilization of family planning services among women of reproductive age at Fort Portal Regional Referral Hospital (FPRRH) Kabarole district. Methodology This was a descriptive cross-sectional study that employed a random sampling method to select the participants and its target population was women of reproductive age, a questionnaire was used to collect data and administered by the researcher, Kish Leslie's formula was used to determine the sample size of 81 respondents. Results. The study results revealed that 45% of the respondents were between the ages of (21-30) years, 55% were married, 45% were Batooro, 40% were housewives, 100% of respondents had some knowledge about family planning(FP), 40% got information from media, 39% of the health worker's attitude was excellent and 67.45% women had never missed their FP option at any of their visits. The majority 75.3% of the women were supported by their partners to use FP and most 65.4% of the women were employed though 60% of women's cultures were against the use of FP. Conclusion. The study results revealed that all the respondents had some knowledge about FP, the majority of the health worker's attitude was excellent and provided enough information to the clients, and most of the women were supported by their partners to use FP though most cultures were against it. Recommendations. From the study, it is recommended that women should seek FP services from government facilities and the Ministry of Health should extend FP services to the lowest health centers like HC II